Determinants of practice of blood donation among undergraduate students of Ebonyi State University Abakaliki, Southeast Nigeria - Edmund Ndudi Ossai; Nelson C Eze; Okwudiri Chukwu; Ugochinyere A Uguru; Ezinne C Ukpai; Ezeogo Ihere (Archives of Community Medicine and Public Health - Peertechz Publications, 2018)
Objective: Aim of study was to determine the factors affecting the practice of blood donation among undergraduate students of Ebonyi State University Abakaliki, southeast Nigeria. Methods: A descriptive cross sectional study design was employed. A three stage sampling technique was used to select 300 students of the institution. Information was obtained using a self-administered questionnaire. Outcome measure of the study is the proportion of the students that has ever donated blood. Good knowledge of blood donation was determined by the proportion of students who correctly answered seven of the ten variables used to assess knowledge. Results: The mean age of the students was 23.2±3.0 years and majority, 60% were females. Majority, 86.7% were aware of blood donation. Majority, 69.3% had good knowledge of blood donation. A minor proportion, 36.3% were certain blood in blood bank were safe, while 59.3% were willing to donate blood in the future. A minor proportion, 13.3% have ever donated blood of which 55% of them have donated once. Major reasons for not donating blood included fear, 53.8%, no interest/ignorance, 19.6% and cultural/ religious belief, 9.2%. Predictors of being a blood donor included being male, (AOR=3.8; 95% CI:1.7-8.2), willingness to donate blood in future, (AOR=3.1; 95% CI:1.3-7.5) and being of low socio-economic status, (AOR=0.4; 95% CI:0.2-0.9). Conclusions: Majority of respondents had good knowledge of blood donation but only a minor proportion has ever donated blood, however, majority were willing to donate blood in the future. The major barriers to the practice of blood donation among the students were based on misconceptions and lack of information. There is the need for adequate public enlightenment and regular blood donation awareness campaigns in the university and the society at large. The aim of such campaigns which should emphasize the benefi ts of blood donation would be to target those who are willing to donate blood in the future as they could be the mainstay of blood donation if properly motivated especially in developing countries.